The Chicago ring-billed gull damage management project - Bloomquist, Michelle L; Hartmann, John W; Engeman, Richard M; Guerrant, Travis G; Beckerman, Scott F (PeerJ Preprints, 2016)
The population of ring-billed gulls in the upper Midwest has increased exponentially in recent decades leading to a variety of conflicts including property damage, negative economic impacts, threats to human safety, and potential threats to human health. Some studies have suggested a link between gull fecal droppings and elevated Escherichia coli levels in water, which result in swim advisories on public beaches. The objectives of the Chicago ring-billed gull damage management project were to reduce the local production of ring-billed gulls, to evaluate the affects that limiting gull production has on the use of beaches by gulls, and to reduce the severity of conflicts with gulls including the issuance of swim advisories. Between 2007 and 2014, we applied corn oil to 52 - 80% of nests in several gull colonies in Chicago and successfully reduced hatching success and subsequent fledging. It is estimated that we prevented the production of between 77,314 and 183,621 ring-billed gulls since initiation of the project. The number of hatch year gulls observed on Chicago’s beaches during 2008 through 2014 has consistently been less than during the initial year of egg oiling, 2007. The reduction in the number of gulls using Chicago beaches has contributed to a reduction in conflicts with gulls, including a decrease in the frequency of swim advisories on Chicago’s beaches in comparison to 2006.
Keywords: E. coli contamination; bacterial exceedances; Larus delawarensis; population monitoring; swim advisories; ring-billed gull; swim bans